Maternal Risk Factors Associated with Preterm Births among Pregnant Women in Mogadishu, Somalia - Abdifetah Ibrahim Omar; Amina Dahir Mohamed; Mohamed Garad Farah; Ismail Abukar Mahad; Suban Abdullahi Mohamed; Abyan Hassan Dimbil; Nadifo Salad Mohamud; Fowziya Ahmed Abshir; Umayma Abdinasir Abdulkadir (MDPI AG, 2022)
Background: Premature birth impacts millions of newborns annually. Sixty percent of the world's preterm births occur in Sub-Saharan Africa and South Asia. Somalia's premature birth rates and maternal risk factors are poorly studied; hence, this study aims to identify maternal risk factors related to premature births in Mogadishu, Somalia. Methods: This unmatched case-control study was conducted at four maternity hospitals in Mogadishu, Somalia. The cases were newborns with gestational ages of less than 37 weeks; controls were newborns with gestational ages of 37 to 42 weeks. All were live singletons. Cross-tabulation and binary logistic regression were used to analyze the data; a p-value of 0.05 was deemed statistically significant. Result: Of the total of 499 newborns, 70 were cases, and 429 were controls. Adequate prenatal care, maternal urine analysis, tetanus toxoid (TT) vaccination, hemoglobin (Hb) measurement, ultrasound monitoring, intake of iron + folic acid (IFA) supplement, blood pressure (BP) measurement during the current pregnancy, as well as partograph usage during labor all significantly decreased risk of having premature births. A prior history of preterm delivery and preeclampsia, obstetric complications, and female genital mutilation (FGM) significantly increased the risk of preterm births. Conclusion: The utilization of antenatal care services, use of a partograph, obstetric complications, and prior history of premature birth and preeclampsia had a substantial effect on preterm birth rates. This study identifies female genital mutilation (FGM) as a previously unidentified risk factor for preterm birth that needs additional investigation.